2006
DOI: 10.1207/s15327825mcs0901_4
|View full text |Cite
|
Sign up to set email alerts
|

Letters to the Editor in the "War on Terror": A Cross-National Study

Abstract: This article analyzes discursive patterns in a cross-national sample of letters to the editor from the 12 months following the 2001 attacks on the World Trade Center and the Pentagon. Using the techniques of traditional content analysis and Critical Discourse Analysis, the study examines the degree to which letters published in The New York Times, The Times of London, and The Australian serve to support or challenge state practices in the U.S.-led "war on terror." The analysis reveals marked similarities in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 12 publications
1
16
0
2
Order By: Relevance
“…The increase in citizens' educational level may also contribute to the public's higher level of political awareness (Wickrama & Mulford, 1996) and lead them to actively respond to media coverage. For example, letters to editors is one important channel of audience feedback, and sometimes carries they criticism that can promote changes in the newsroom (Hogan, 2006). Reader, Stempel, and Daniel (2004) surveyed 1,017 U.S. adults and found that better educated citizens are more likely to write letters to editors.…”
Section: Education Level Versus Bribery For News Coveragementioning
confidence: 99%
“…The increase in citizens' educational level may also contribute to the public's higher level of political awareness (Wickrama & Mulford, 1996) and lead them to actively respond to media coverage. For example, letters to editors is one important channel of audience feedback, and sometimes carries they criticism that can promote changes in the newsroom (Hogan, 2006). Reader, Stempel, and Daniel (2004) surveyed 1,017 U.S. adults and found that better educated citizens are more likely to write letters to editors.…”
Section: Education Level Versus Bribery For News Coveragementioning
confidence: 99%
“…Para los lectores de los matutinos, resultaban tan peligrosas para el proyecto colectivo de nación, las actuaciones públicas de personajes de la vida nacional como Piedad Córdoba, militante de la izquierda y José Obdulio Gaviria, de la derecha. Lo dicho resulta coincidente con los estudios sobre cartas llevados a cabo por Lemert y Larkin (1979), Southgate y Hopwood (1999), Hessing (2003), Richard son y Franklin (2004), Hogan (2006) y Young (2011, en donde también se advierten referencias a posturas encontradas entre los lectores y actores sociales identificados con claridad en los textos.…”
Section: Discussionunclassified
“…Algunos de los principales es tudios dan cuenta que las misivas han sido utilizadas para medir la movilización ciu dadana en temas sensibles en lo público. Hogan (2006) las estudió para cuenta del nivel de apoyo que el gobierno de Estados Unidos recibió en su lucha contra el terro rismo luego de los atentados del 11 septiembre de 2001. Hessing (2003) y Young (2011, así como Lemert y Larkin (1979), emplearon las cartas para medir el apoyo del público en temas ambientalistas en Canadá y Estados Unidos, respectivamente.…”
unclassified
“…1 See also these studies of media coverage of computer technology: Hogan (2006), which combines traditional content analysis and critical discourse analysis, and Thurlow's (2006) (Kelly, 2001). 3 Although the two editorial texts do not represent great variety in publication dates, they were selected based on evidence in the preliminary reading suggesting they demonstrated relevant frame characteristics that remained constant across the time period, a method suggested by Fairclough (1993).…”
Section: Notesmentioning
confidence: 99%